2021
DOI: 10.1186/s40537-021-00500-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of knowledge extraction in predicting customer churn in B2B

Abstract: Data mining techniques were used to investigate the use of knowledge extraction in predicting customer churn in insurance companies. Data were included from a health insurance company for providing insight into churn behaviour based on a design and application of a prediction model. Additionally, three promising data mining techniques were identified for the prediction of modeling, including logistic regression, neural network, and K-means. The decision tree method was used in the modeling phase of CRISP-DM fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Knowing the risk period will be useful for the business in terms of preventing the customer churn by developing personalized offers and providing additional incentives for current clients. The conclusions of the research by Jamjoom (2021) prove that data mining methods can be highly successful in finding hidden insights and highlighting customer's information. Besides, it is found that each model works effectively with a different training dataset.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Knowing the risk period will be useful for the business in terms of preventing the customer churn by developing personalized offers and providing additional incentives for current clients. The conclusions of the research by Jamjoom (2021) prove that data mining methods can be highly successful in finding hidden insights and highlighting customer's information. Besides, it is found that each model works effectively with a different training dataset.…”
Section: Literature Reviewmentioning
confidence: 83%
“…NN and SVM performed both best with an accuracy of 83.7%. Jamjoom [44] carried out an analysis of customer churn in B2B. Data from a health insurance company were included for providing insights into churn behavior based on a design and application of a prediction model.…”
Section: Customer Churn Prediction Methodsmentioning
confidence: 99%
“…Looking at previous studies of customer churn prediction models in the financial sector, research on prediction models was conducted in Korea, mainly in banks and the credit card industry with a large number of customers because academic access to financial data is relatively difficult compared to overseas [ 20 ]. Most of the preceding studies were divided into those that present a method of improving predictive performance by applying various machine learning algorithms [ 21 , 43 ] and those that segment the customer marketing indicators using predicted results [ 22 – 24 ].…”
Section: Related Workmentioning
confidence: 99%